Speed, agility, and musculoskeletal fitness are independently associated with areal bone mineral density in children - Mello, Júlio B.; Rodríguez-Rodríguez, Fernando; Gracia-Marco, Luis; Teodoro, Juliana L.; Gaya, Anelise R.; Gaya, Adroaldo C. A. (Frontiers in Physiology, 2023)
Background There is still little understanding of the associations between physical fitness variables and bone health in children taking into account key confounders. Aim The aim of this study was to analyse the associations between performance in tests of speed, agility and musculoskeletal fitness (power of upper and lower limbs) with the bone mass of different regions in children, considering the adjustment to maturity-offset, lean percentage and sex. Methods Cross-sectional study design. The sample consisted of 160 children aged 6-11 years. The physical fitness variables tested were: 1) Speed, assessed with the running test at a maximum speed of 20 meters; 2) Agility, assessed through the 4x4 meter square test; 3) Lower Limb Power, assessed using the standing long jump test, and 4) Upper Limb Power, assessed using the 2 kg medicine ball throw test. Areal bone mineral density (aBMD) was obtained from the analysis of body composition by DXA. Simple, and multiple linear regression models were performed in SPSS software. Results In the crude regression analyses the results indicated a linear relationship between all physical fitness variables and aBMD in all body segments; But maturity offset, sex and lean mass percentage seem to have an effect on these relationships. Except for the upper limb power, the other physical capacities (speed, agility and lower limb power) are associated with aBMD in at least three body regions in the adjusted analyses. These associations occur in spine, hip and legs regions, and the aBMD of legs presents the best association magnitude (R²). Conclusion There is a significative association between speed, agility and musculoskeletal fitness, specifically lower limb power, and aBMD. That is, the aBMD is a good indicator between fitness and bone mass relationship in children, but is important to consider what fitness variable and what skeletal region.